LABSim: A dynamic life course model of individual life course trajectories for Italy - Matteo Richiardi; Patryk Bronka (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
LABSim is a rich dynamic microsimulation model of individual and household life course events, which means that it simulates individual units over time and allows for individual characteristics to be changed according to the processes specified within the model. One of the key innovations in LABSim is its linkage with EUROMOD, a static tax-benefit microsimulation model used to evaluate the immediate distributional impact of policy changes (the "morning after" effect). The static model allows ex-post evaluation of policies, as well as ex-ante evaluation of hypothetical policy changes. When combined with the dynamic model, the policies are applied to an evolving population and evaluated over time. Users of LABSim can construct as many policy scenarios as they wish by using a bespoke simplified EUROMOD graphical interface, directly called from within the LABSim application.1 They can then specify which policy scenario to use in each simulated year. The integration of a static tax-benefit calculator within a dynamic context makes LABSim quite rare in the literature. Indeed, to the best of our knowledge there are only two other models which to some extents are comparable to LABSim. One is LINDA (van de Ven, 2018), developed at the National Institute of Social and Economic Research on UK data, while another one is T-DYMM, the dynamic model developed by the Italian Treasury. LINDA is characterised by a sophisticated modelling of the individual intertemporal decision-making process (labour supply and savings) but covers fewer dimensions than LABSim. As for T-DYMM, very little is known apart from a 2011 project report (Ministry of Treasury, 2011). Looking at the available documentation it appears that the model does not include a health dimension, which is a significant source of life course risk. Internal sources suggest that the model is currently under a major redevelopment. The structure of this note is as follows. Section 2 describes the inputs required by the model, while Section 3 discusses the model structure and the specification of each process. Section 4 presents validation statistics and discusses model uncertainty. Session 5 analyses some of the model outputs, while Section 6 concludes.
Keywords: 330; Public Policy; Welfare Benefits; Taxation; Life Course Analysis; Microsimulation